Mengelola Keseimbangan Karir dan Pendidikan: Studi Fenomenologi Ibu yang Bekerja Sambil Kuliah S3 di Universitas Gadjah Mada - Jurnalista, Rasa Cinta; Afandi, Ardian Rahman (Personifikasi: Jurnal Ilmu Psikologi, 2025)
A mother who works while pursuing PhD faces significant challenge achieving work-life balance due to academic demands, work pressure, and maternal responsibilities. The absence of social support and effective time management strategies can lead to burnout, stress, and a decline in well-being. This research aims to explore the dynamics of work-life balance faced by mothers studying PhDs, focusing on the influence of their social roles on individual well-being. Using a qualitative approach, this research adopts in-depth interview methods to four participants who chosen by a purposive sampling and interpretative phenomenological analysis to explore mothers studying doctoral studies, realizing their dual roles as mothers, students, researchers, and colleagues. The research result show that perceptions of multiple roles and work-life balance are subjective and influenced by individual context. These findings provide new insight into how dual roles affect the well-being of mothers who are also PhD students and present the basis for developing more effective strategies for managing work-life balance among graduate students.